Building Engagement in Facebook: A Case Study with Utah State University Extension Sustainability - Kenna R Kesler; Kelsey Hall; Debra Spielmaker; Roslynn G. H. Brain McCann (Journal of Applied Communications, 2021)
In order to stay relevant in an online world, Extension must properly use social networking platforms to effectively reach diverse audiences regarding agricultural and natural resource issues. However, few studies have focused on how Extension uses Facebook to effectively accomplish its goal. This study’s purpose was to explore how Utah State University Extension Sustainability uses Facebook to engage followers. The researchers conducted a quantitative content analysis of 504 messages posted to the USU Extension Sustainability Facebook page. Graphics and links were the most common post characteristics used by the organization. Text-only posts and posts containing videos were utilized the least. Food was the most common area of sustainability discussed on the page. Posts containing videos, shared content, or that tagged other Facebook pages in messages experienced statistically significantly higher user engagement than posts without those characteristics. Posts containing hashtags experienced statistically significantly lower engagement. Neutral sentiment appeared in the majority of posts. Additionally, information seeking was the most dominant communicative function among the posts. Neither the type of sentiment nor communicative functions were significantly connected to engagement. Future research should determine changes in knowledge, attitudes, intentions, and behavior as a result of exposure to, and engagement with, the Facebook page. Additionally, a qualitative study determining consumers’ attitudes toward Facebook content can provide a deeper understanding of the audience’s thought processes and content preferences. Page administrators should craft engaging content that builds community among followers.
Keywords: Facebook; engagement; post characteristics; sentiment; communicative functions